(untitled) (Ameghiniana, 2014)
The new species Ceratophrys ameghinorum is described. This species is distinguished from other species of this genus in the presence of a triangular squamosal otic plate that is projected markedly above the dorsal surface of the skull. The external edge of the otic plate bears a longitudinal crest that ventrally turns into a lateral wall. In lateral view, the length of the otic ramus represents more than 55% of the length of the ventral ramus. The atlas bears a pair of cotyles with discontinuous articular surfaces. The species C. prisca Ameghino is considered species inquirenda.